Pengaruh Tangibel, Reliability, Responsiveness, Assurance, Empathy Terhadap Pelayanan Automatic Teller Machine Bank Central Asia Di Yogyakarta - Asih Ayu Subekti (Fakultas Ekonomi Universitas Sarjanawiyata Tamansiswa, 2012)
This study aims to determine whether tangible, Reliability, Responsiveness, Assurance, Empathy affect the service provided BCA either simultaneously or partially. This research using the descriptive nature of the research. The population in this study is user BCA ATM in Yogyakarta and sample as many as 50 people. The variables in this study consists of tangible (X^1), Reliability (X^2), Responsiveness (X^3), Assurance (X^4), Empathy (X^5), and services (Y). Methods of data collection using questionnaires. The results showed:1) There is a positive and significant correlation between BCA ATM user satisfaction with the services provided by Bank Central Asia is reflected in the regression equation was as follows: There is a positive and significant correlation between tangible (X^1 and services (Y), significant can be seen with significant value = 0.000